Pengembangan Mutu Sekolah Melalui Pendekatan TQM - Nur Aimmatul Aula; Hindun Maisaroh; Umul Lathifah (Ar-Rosikhun: Jurnal Manajemen Pendidikan Islam, 2021)
Efforts in improving the quality of education in its management system emphasize the independence and creativity of schools in processing potential educational resources through collaboration with the government and the community in making decisions to meet the goals of improving school quality. To become a quality educational institution, of course there are efforts made from all elements of the institution. One of the efforts made is by implementing Total Quality Management (TQM). This paper examines the TQM approach in developing a quality school model. The achievements made by a quality school can be seen in the context of student achievement, both academic and non-academic. This research method uses a qualitative descriptive approach, and the type of research used is library research, which is collecting data or scientific papers related to the object of research or data collection that is library in nature. The results found There is a trilogy of managerial processes in improving quality, namely quality planning, quality control, quality improvement.